2008
DOI: 10.1093/ndt/gfm831
|View full text |Cite
|
Sign up to set email alerts
|

Hypernatraemia in critically ill patients: too little water and too much salt

Abstract: Hypernatraemia seems to develop in the ICU because various factors promote renal water loss, which is then corrected with too little water or overcorrected with relatively hypertonic fluids. Therapy should therefore rely on adding electrolyte-free water and/or creating a negative sodium balance. Adjustments in intravenous fluid regimens may prevent hypernatraemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
173
2
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(200 citation statements)
references
References 30 publications
11
173
2
14
Order By: Relevance
“…En la literatura se ha descrito que esta asociación se debe a que en las etapas tardías de la sepsis se provoca un déficit de la hormona antidiurética mientras que en la IRA existe una mala capacidad de concentrar la orina (3)(4)(5). Sin embargo, al analizar estos datos mediante regresión logística binaria, las variables no tuvieron significancia estadística en el modelo final sostenible de asociación con hipernatremia y una de ellas, la IRA, mostró ser una variable de confusión con el uso de diuréticos, que sí mostró valor significativo por sí misma.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En la literatura se ha descrito que esta asociación se debe a que en las etapas tardías de la sepsis se provoca un déficit de la hormona antidiurética mientras que en la IRA existe una mala capacidad de concentrar la orina (3)(4)(5). Sin embargo, al analizar estos datos mediante regresión logística binaria, las variables no tuvieron significancia estadística en el modelo final sostenible de asociación con hipernatremia y una de ellas, la IRA, mostró ser una variable de confusión con el uso de diuréticos, que sí mostró valor significativo por sí misma.…”
Section: Discussionunclassified
“…En el 2007, Lidner et al, describieron en una Unidad de Cuidados Intensivos, que la presencia de la hipernatremia se asoció con una mayor mortalidad (entre el 39 y 43%) en relación a los pacientes que no la tuvieron (24%) (2), observación totalmente coincidente con otros estudios anteriores y posteriores que describen igualmente letalidad alrededor del 33,5% en pacientes con hipernatremia contra 7,7% de pacientes con valores normales de sodio sérico, concluyendo que la hipernatremia es un factor de independiente de riesgo de muerte intrahospitalaria (OR 1,97, p<0,001) (3)(4)(5).…”
Section: Introductionunclassified
“…Niedobór wazopresyny występuje u ⅓ pacjentów w późnych fazach sepsy oraz wstrząsu septycznego i stanowi niezależny czynnik prognostyczny zwiększonej śmiertelności na OIT [32]. Niewykluczone, że SAE może prowadzić do zaburzeń funkcjonowania regionalnego w mózgowiu, zwłaszcza w podwzgórzu i przysadce, które regulują równo-wagę wodną i elektrolitową.…”
Section: Zaburzenia Metaboliczne I Elektrolitoweunclassified
“…65 Similar to hyponatremia, a diagnosis of hypernatremia has been associated with an increased risk for hospital death. 64,65,[67][68][69] However, it may be difficult to separate the contribution to mortality of hypernatremia alone from that of the underlying disease process and overall illness severity. Nonetheless, mortality has been shown higher for critically ill patients with hypernatremia (serum [Na ? ]…”
Section: Hypernatremiamentioning
confidence: 99%
“…64 In addition, Polderman et al 66 showed that the risk of hospital death was higher for patients with hospital-acquired hypernatremia than for patients with hypernatremia present at the time of admission to the intensive care unit (32% vs. 20%, respectively, P \ 0.001). Recently, Hoorn et al 68 showed hypernatremia (serum [Na ? ] C 150 mmol l -1 ) was independently associated with higher mortality (48% vs. 10%, P \ 0.001).…”
Section: Hypernatremiamentioning
confidence: 99%